[PP.14.10] CARDIOVASCULAR REMODELING IN MILD HYPERTENSION: THE ROLE OF URIC ACID. (September 2017) - Maresca, A.; Mongiardi, C.; Montalbetti, L.; Grossi, A.; Pierobon, V.; Tandurella, N.; Agostinis, M.; Tavecchia, L.; Moretti, S.; Cavallaro, G.; Grandi, A.M.; Guasti, L.
Abstract : Objective: It has been observed in animal models that uric acid can induce the growth of cardiomyocytes and the development of interstitial fibrosis. However, few clinical studies have shown conflicting results about the relationship between serum uric acid (SUA) and cardiovascular remodeling. Aim of this study was to evaluate the relationship between uric acid levels and cardiac, aortic and carotid morphofunctional parameters in a cohort of not treated mild hypertensive patients. Design and method: We enrolled 246 mild hypertensive patients (113 males and 133 females) without known cardiovascular disease, gout, diabetes mellitus and renal failure, matched for age and BMI. For each subject, we evaluated office and 24 h BP. Each patient underwent arterial tonometry (central blood pressure), echocardiography (left ventricular mass, thoracic aortic diameters), carotid (intima media thickness, IMT) and abdominal aortic ultrasonography and blood tests (SUA). Results: SUA levels were higher in men than women (5.3 ± 1.3 vs 4.8 ± 1.4 mg/dL p 0.04), but there was not a significant difference when hypertensive patients were compared to normotensive. Univariate analysis showed a significant correlation between serum uric acid levels and left ventricular mass (r = 0.24, p = 0.001) and relative wall thickness (r = 0.168, p = 0.01) suggesting a possible role of uric acid in the development of concentric geometry. We showed a significant correlation between 24 h SBP and 24 h DBP with SUA (p = 0.001 and p = 0.04). In a multivariate analysis we confirmed the correlation of left ventricular mass with 24 h SBP (beta = 0.169, p = 0.05) and SUA (beta = 0.240, p = 0.007). No correlation was found between SUA and carotid IMT, thoracic (root and ascending) and abdominal aortic diameters. Conclusions: In conclusion, our results may suggest a possible role of uric acid in the onset of structural and functional remodeling of left ventricle. Thoracic and abdominal aortic diameters and carotid IMT did not show any correlation with uric acid. These data need further confirmation in prospective studies.